Los Frameworks de Javascript - Herrera Rivas, José Luis (2022)
Currently, the advancement of various technologies has allowed various activities to be carried out in which developers and even those who wish to be professionals in this area work hard to learn about everything in terms of technological innovations and that is why reason that in these times for the elaboration of a web application the diverse pre-existing structures are used that benefit the programmers as it is the case of the frameworks that make the work that is elaborated in its layout be improved and very well structured in a way that when using it, the creation time is less than when starting from scratch and without any pre-established structure so that when it exists, it directly benefits its productivity. The use of javascript frameworks is considered very important because these are essential bases for the creation of web applications which will make the user have all the necessary tools for navigation in it so that this guarantees an adequate experience in the web. use of the application. The objective is to know how the use of javascript frameworks affects to guarantee the proper functioning of web applications developed by developers, in addition, the development of this case study is carried out in which it is based on the bibliographical citations that are obtained from the various sources, the descriptive methodology is applied and finally it is concluded by stating the importance of the use of the javascript framework for the creation of web applications.